Urgensi Public Trust dalam Mempengaruhi Pola Perilaku Kepatuhan Masyarakat pada Masa Pandemi Covid-19 di Indonesia - Aulia Hanadita Balkis; Bryan Keith Sangap Hutagalung; Nur Harfi Oktaviani (Universitas Sebelas Maret, 2021)
To face the COVID-19 pandemic, various efforts have been made by the Government of Indonesia. Starting from the implementation of Large-Scale Social Restriction (PSBB) and promoting vaccination programs for adults and children aged 12 years and upwards. To ensure the efectiveness of every policy and program, it is necessary to build public trust in the government which will lead to public compliance to government’s policies in order to cope with COVID-19 in Indonesia. The method of data collection conducted in this paper is through the study of literature from a variety of literature that are relevant to the topic of the research done by the author. The findings showed that there is an anomaly relationship between the trust and compliance of the public. The high trust of the community in the government are being followed by public’s attitudes that lack of responsibility. It happens because the public feels the government is able to control this pandemic. So the compliance of the community towards the government policies in order to cope with COVID-19 tend to be low.